设等比数列{an}的前n项和Sn,首项a1=1,公比q=f(λ)=
(Ⅰ)证明:Sn=(1+λ)-λan; (Ⅱ)若数列{bn}满足b1=
(Ⅲ)若λ=1,记cn=an(
|
(Ⅰ)证明:Sn=
=a1(1-qn) 1-q
=(1+λ)[1-(a1[1-(
)n]λ 1+λ 1- λ 1+λ
)n]=(1+λ)-λ(λ 1+λ
)n-1λ 1+λ
而an=a1(
)n-1=(λ 1+λ
)n-1所以Sn=(1+λ)-λan(4分)λ 1+λ
(Ⅱ)f(λ)=
,∴bn=λ 1+λ
,∴bn-1 1+bn-1
=1 bn
+1,(6分)1 bn-1
∴{
}是首项为1 bn
=2,公差为1的等差数列,1 b1
=2+(n-1)=n+1,即bn=1 bn
.(8分)1 n+1
(Ⅲ)λ=1时,an=(
)n-1,∴cn=an(1 2
-1)=n(1 bn
)n-1(9分)1 2
∴Tn=1+2(
)+3(1 2
)2++n(1 2
)n-1∴1 2
Tn=1 2
+2(1 2
)2+3(1 2
)3++n(1 2
)n1 2
相减得∴
Tn=1+(1 2
)+(1 2
)2++(1 2
)n-1-n(1 2
)n=2[1-(1 2
)n]-n(1 2
)n1 2
∴Tn=4-(
)n-2-n(1 2
)n-1<4,(12分)1 2
又因为cn=n(
)n-1>0,∴Tn单调递增,1 2
∴Tn≥T2=2,故当n≥2时,2≤Tn<4.(13分)